'Green' Growth, 'Green' Jobs and Labor Markets - Bowen, Alex (World Bank, Washington, DC, 2012)
The term 'green jobs' can refer to employment in a narrowly defined set of industries providing environmental services. But it is more useful for the policy-maker to focus on the broader issue of the employment consequences of policies to correct environmental externalities such as anthropogenic climate change. Most of the literature focuses on direct employment created, with more cursory treatment of indirect and induced job creation, especially that arising from macroeconomic effects of policies. The potential adverse impacts of green growth policies on labor productivity and the costs of employment tend to be overlooked. More attention also needs to be paid in this literature to how labor markets work in different types of economy. There may be wedges between the shadow wage and the actual wage, particularly in developing countries with segmented labor markets and after adverse aggregate demand shocks, warranting a bigger and longer-lasting boost to green projects with high labor content. In these circumstances, the transition to green growth and job creation can go hand in hand. But there are challenges, especially for countries that have built their industrial development strategies around cheap carbon-based energy. Induced structural change, green or otherwise, should be accompanied by active labor market policies.